Burnout syndrome during the development of pre-professional practices in university students - Chui-Betancur, Heber Nehemias; Gutierrez, Fredy Sosa; Tapia-Centellas, Yudy Yaneth; Jinez-Garcia, Esther Lidia; Huisa, Ruth Mery Cruz; Achata-Cortez, Cesar Augusto; Yucra-Quispe, Teófilo; Pino, Efrain Humberto Yupanqui (O Mundo da Saúde, 2025)
Burnout is a highly impactful issue among university students. The objective of this study was to compare the dimensions of burnout during the development of pre-professional practices among Secondary Education students at the Universidad Nacional del Altiplano de Puno. The study employed a quantitative approach with a comparative design and included 230 students. To assess burnout syndrome, the MBI instrument, composed of 22 items, was used. The results of the analysis of variance (ANOVA) indicate significant levels of burnout across the three dimensions analyzed: Emotional Exhaustion (F = 80.154, p < 0.001), Depersonalization (F = 206.161, p < 0.001), and Low Personal Accomplishment (F = 90.848, p < 0.001). The pre-professional practices carried out during semesters V, VI, VII, VIII, IX, and X are associated with higher emotional exhaustion, increased depersonalization, and a lower sense of personal accomplishment. This phenomenon may be related to the increasing burden of responsibilities and the direct exposure to complex and stressful situations in the work environment, which generate progressive psychological strain. Furthermore, the continuous exposure to emotional demands and pressure to meet professional standards may negatively affect motivation and the sense of accomplishment — key factors for overall well-being.